Transfer Omega-3 Melalui Kapsulisasi dan L-Karnitin Pengaruhnya Terhadap Kandungan Asam Lemak Daging dan Sate Kambing - Sudibya, Sudibya (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2008)
The objective of this study were to find out and to compare the effect of supplementation of L-carnitine and tuna fish oil and lemuru fish oil  on  fatty acid saturated, fatty acid non saturated  concentration  and peroksida, TBA  number.   The materials used were 20 male PE (Peranakan Etawah) goats of 2 until 3 month old and 15.5-23.5 kilogram body weight. The feedstuff used were wild grass, yellow corn, rice bran, soy bean meal, coconut meal, mineral premix. L-carnitine, tuna fish oil and lemuru fish oil. The method of the research was experimental in vivo using Completely Randomized Blok Design. There were 4 treatments in each treatment and 5 replication. Treatment consisted  of P0= control ration, P1=P0 +L-carnitine 50 ppm, P2=P1 + tuna fish oil 5 ml or equal with 4% in the ration, and P3=P1+ lemuru fish oil 5 ml or equal with 4% in the ration.  The variables measuared  fatty acid saturated, fatty acid non saturated  concentration  and peroksida number..            The results of variance analysis showed that the effect of supplementation of tuna fish oil and lemuru fish oil  (P2 and P3) in the rations contain 50 ppm L-carnitine were  significantly (P<0.01) on faty acid saturated, faty acid non saturated  concentration  and peroksida number.The conclusion of this research shows that the supplementation of 50 ppm L-carnitine, tuna and lemuru fish oil 5ml that was equal to 4% in goat rations can  incrase non saturated fatty acid from 59,74 to 67,36%,  than to decreased saturated fatty acid from 40,26 to 32,64 %. Proces burned of meat goat to increase peroxida from 0.1437 until 0.1615 miliequivalen/kg and malonaldehyde from 1,807 until 2,440 mg/kg  then to decrease concentration omega-3 fatty acid from 5,957 until 5,945%. Key words :  saturated fatty acid, non saturated fatty acid , L-carnitine, tuna, lemuru                 fish oils